Cystic Fibrosis Revisited – a Review Study - Klimova, Blanka; Kuca, Kamil; Novotny, Michal; Maresova, Petra (Medicinal Chemistry, 2017)
Background: Cystic fibrosis (CF) is an incurable, chronic disease, which causes severe damages to respiratory and digestive tracts. It is the most common genetically inherited disease among caucasians. This disease is caused by defects in CF genes, the so-called mutations in cystic fibrosis transmembrane conductance regulator (CFTR) gene population. At present over 100,000 people suffer from this disease worldwide. Objective: The purpose of this review study is to describe the pathophysiology of CF and provide the latest information on its diagnosis and treatment therapies with respect to the improvement of patient’s quality of life and emphasis on targeted specialized care. Method: The methodological approaches include a method of literature review of available sources exploring the issue of cystic fibrosis both from a global and specific perspective point of view. A search was performed in the databases PubMed, MEDLINE, Web of Science, Scopus, Springer and ScienceDirect. Furthermore, other sources cited in the analyzed studies were also examined. On the basis of evaluation of these literature sources, the research issue was explored. Results: The main benefits (e.g., specialized centres for the treatment of CF exist or a new breakthrough in the gene therapy of CF has been made) and limitations (e.g., comorbidity of CF, lifelong and costly treatment, or adverse impact on patient’s and caregiver’s quality of life) in the treatment of narcolepsy are highlighted. Conclusion: CF requires an integrated treatment approach in specialized CF centers, involving various factors contributing to a better patient’s state of health in the form of relevant and well-balanced non-pharmacological and pharmacological therapies. In addition, further large scale clinical trials are needed in order to develop compounds that are aimed at the most common classes of CFTR.
Keywords: pathophysiology